94kvibezz
Rozwiązane

1) Wyznacz podane wyrażenie, jeśli
A = -5x + 2y - 6 i B= 6 - 3x - 4y.
a) A + B
c) B-A
b) A - B
d) -A — В



1 Wyznacz Podane Wyrażenie Jeśli A 5x 2y 6 I B 6 3x 4y A A B C BA B A B D A В class=

Odpowiedź :

1)

A = -5x + 2y - 6

B = 6 - 3x - 4y

a) A + B = (-5x + 2y - 6) + (6 - 3x - 4y) =  -5x + 2y - 6 + 6 - 3x - 4y = -8x - 2y

b) A - B =  (-5x + 2y - 6) - (6 - 3x - 4y) =  -5x + 2y - 6 - 6 + 3x + 4y

= -2x + 6y - 12

c) B - A = (6 - 3x - 4y) - (-5x + 2y - 6) = 6 - 3x - 4y + 5x - 2y + 6 = 12 + 2x - 6y

d) -A -B = -(-5x + 2y - 6) - (6 - 3x - 4y) = 5x-2y+6-6+3x+4y = 8x+2y